Autonomous Coastal Land Cover Assessment Using Polarimetric Decomposition of SAR Data - Bambang H. Trisasongko (Journal of Engineering and Technological Sciences, 2011)
The  paper  reports  an  experiment  on  classification  using  fully polarimetric SAR data.  Many  reports have been presented mentioning test sites in  temperate  regions  utilizing  polarimetric  SAR  data  from  airborne  and/or spaceborne SAR sensors. However, few  studies are dedicated  to  tropical region which highly dynamic land uses are  observed.  Using the AirSAR Sungai Wain fully polarimetric data, capability to extract features in coastal region has been demonstrated  by  an  unsupervised  classification  technique  fed  by  the  CloudePottier decomposition theorem.